Adherence to Dual Antiplatelet Therapy After Coronary Stenting: A Systematic Review. Issue 8 (2nd May 2014) - Czarny, Matthew J.; Nathan, Ashwin S.; Yeh, Robert W.; Mauri, Laura
ABSTRACT Background Adherence to dual antiplatelet therapy (DAPT) is critical after coronary stenting. Although adherence rates are frequently assessed in clinical trials, adherence rates in the unselected population recommended for treatment but beyond clinical trials are largely unknown. Therefore, we performed a systematic review of published observational studies to describe rates of DAPT adherence, trends in DAPT use over time, and patient‐level factors associated with nonadherence. Hypothesis DAPT adherence declines with increasing time after drug‐eluting stent implantation. Methods PubMed, Cumulative Index to Nursing and Allied Health Literature, Embase, and Web of Knowledge were searched through November 20, 2012 for studies including patients receiving 1 or more drug‐eluting stents and reporting the use of aspirin and/or thienopyridines, or assessing factors associated with nonadherence to DAPT after bare metal or drug‐eluting stent placement. Results We included 34 studies in the description of DAPT adherence and 11 studies in the description of factors associated with nonadherence. Adherence to DAPT and thienopyridines was high at 1 month but declined by 12 months. Aspirin adherence was at least 90% throughout. Factors associated with nonadherence included bleeding, lower education level, immigrant status, and lack of education regarding DAPT. Conclusions DAPT adherence is suboptimal at 12 months, and interventions to increase adherence should focus on reducing bleeding risk and improving communication between patients and physicians.